EVALUASI KEBIJAKAN JAMINAN PERSALINAN (JAMPERSAL) DI PUSKESMAS TALISE KOTA PALU - Suharsoyo, Suharsoyo (Katalogis, 2014)
The Objectives of the research were to : (1) Analyze the evaluation of birth assurance policyin public health of Talise Palu City. The main theory of policy employed was from William Dunn covering: (1) effectiveness, (2) efficiency, (3) adequateness, (4) equality, (5) responsiveness, (6) accuracy. The research method was qualitative approach.  The  research  setting  was  at  public health of Talise with 6 informants who selected purposively as the sample. The techniques of data collection were interview, observation and documentation. The technique of data analysis employed Miles and Huberman interactive model. Based on the research result, it showed that the implementation of birth assurance policy in public health of Talise had been conducted, however, it was not  as expected. It could be seen from the six criteria, the evaluation of the policy effectiveness had not run effectively because the result given was not maximal; then from efficiency had already been  done well  by conducting  many efforts  and  strategy for  the society to  use the policy by implementing  gathering  pregnant  women  which  the  funding  taken  from  Health  Operational Funding; from adequateness, the public health of Talise had fulfilled human resources and facility of the public health, and from equality, the policy of birth assurance had been given equally to the whole society even though the budget process was still late by the verificator team of City Health Official; from responsiveness, the officer had given satisfying service to the society even though the result and birth assurance budget was still low; and finally from accuracy, it had given benefits to the society by giving pregnancy checking and birthing free and enhancing income for the officers of the health public.